CDKL5 kinase controls transcription‐coupled responses to DNA damage. (4th October 2021) - Khanam, Taran; Muñoz, Ivan; Weiland, Florian; Carroll, Thomas; Morgan, Michael; Borsos, Barbara N; Pantazi, Vasiliki; Slean, Meghan; Novak, Miroslav; Toth, Rachel; Appleton, Paul; Pankotai, Tibor; et al.
Abstract: Mutations in the gene encoding the CDKL5 kinase are among the most common genetic causes of childhood epilepsy and can also give rise to the severe neurodevelopmental condition CDD (CDKL5 deficiency disorder). Despite its importance for human health, the phosphorylation targets and cellular roles of CDKL5 are poorly understood, especially in the cell nucleus. Here, we report that CDKL5 is recruited to sites of DNA damage in actively transcribed regions of the nucleus. A quantitative phosphoproteomic screen for nuclear CDKL5 substrates reveals a network of transcriptional regulators including Elongin A (ELOA), phosphorylated on a specific CDKL5 consensus motif. Recruitment of CDKL5 and ELOA to damaged DNA, and subsequent phosphorylation of ELOA, requires both active transcription and the synthesis of poly(ADP‐ribose) (PAR), to which CDKL5 can bind. Critically, CDKL5 kinase activity is essential for the transcriptional silencing of genes induced by DNA double‐strand breaks. Thus, CDKL5 is a DNA damage‐sensing, PAR‐controlled transcriptional modulator, a finding with implications for understanding the molecular basis of CDKL5‐related diseases. SYNOPSIS: Roles and targets of the neurodevelopmental disease‐linked kinase CDKL5 in the cell nucleus have remained unclear. Phosphoproteomic identification of nuclear CDKL5 substrates now links it to transcriptional silencing of genes close to unscheduled DNA breaks. A cell–based screen for protein kinases recruited to DNA damage sites reveals CDKL5 binding to DNA damage in actively transcribed genomic regions. CDKL5 recruitment requires PARP activity and ongoing transcription, implicating CDKL5 as a coincidence detector sensing both poly(ADP‐ribose) and RNA at DNA breaks. A systematic screen for nuclear targets of CDKL5 identifies proteins involved in transcriptional control and transcriptional elongation. CDKL5 kinase activity is required for transcriptional silencing near unscheduled DNA breaks. Abstract : Phosphoproteomics identification of nuclear CDKL5 substrates implicates the neurodevelopmental disease‐linked kinase in poly(ADP‐ribose)‐mediated silencing at DNA double‐strand breaks.